Oviposition Preferences and Behavior of Wild-Caught and Laboratory-Reared Coconut Rhinoceros Beetle, Oryctes rhinoceros (Coleoptera: Scarabaeidae), in Relation to Substrate Particle Size - Megan Manley; Michael J. Melzer; Helen Spafford (Insects, 2018)
The coconut rhinoceros beetle (CRB), Oryctes rhinoceros (L.) (Coleoptera: Scarabaeidae), has become one of the most important coconut and oil palm pests. This species was detected attacking coconut palms on Oʻahu, Hawaiʻi in December 2013, and an eradication program was initiated. One of the major challenges for eradication has been the identification of new breeding sites. Information on the factors influencing oviposition is needed to aid in finding sites likely to host the immature stages of this insect. In this study, a series of choice tests were conducted to assess the oviposition preferences of both laboratory-reared and wild-caught CRB. Mated females, of both lab-reared and wild-caught beetles, were offered for oviposition a choice between sand and two mulch substrates, one with small and one with large particle sizes. Both types of CRB laid eggs preferentially in substrate of small particle size rather than large and none laid eggs in sand. Lab-reared and wild-caught CRB differed in their oviposition behavior and size. These results can be used to aid in the identification of breeding sites for management programs and eradication efforts.